Population with criminal records and racial disparity in labor markets - Jasmine Boatner (IZA Journal of Labor Policy, 2019)
Background: Although unemployment rates are at historical lows, there is still a persistent gap between unemployment rates in black and white population. Some have proposed that part of the gap for men can be explained by the higher rate of criminal records in the black population. Methods: This analysis aims to use negative binomial regressions and the detailed crime data available from the National Longitudinal Survey of Youth 1997 survey to determine if black men with criminal records appear to be the driving force behind the gap. Results: The author finds that there are significant deviations in labor market outcomes depending on race and ethnicity, even when controlling for a criminal record and premarket skills. Conclusions: Lowering the disproportionate rate at which black men are incarcerated will not in itself eliminate the unemployment gap between white and black men.
Keywords: J01; J64; J71; 330; crime; discrimination; labor market; unemployment